Monday
March 27, 2017

Post a New Question

Posted by on .

(y^2)^-4y^8 simplify

  • pre cal - ,

    y^2 - 4y^8 = y^2 - (2y^4)^2
    = (y + 2y^4)(y - 2y^4)

    formulas a^2 - b^2 = (a + b)(a - b)

  • pre cal - ,

    Or, seeing that the expression as written is meaningless, and assuming the usual carelessness with parentheses,

    (y^2)^(-4) * y^8
    = y^(2 * -4) * y^8
    = y^(-8) * y^8
    = y^(-8+8)
    = y^0
    = 1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question